Effect of Calcium Sulphate Pre-crosslinking on Rheological Parameters of Alginate Based Bio-Inks and on Human Corneal Stromal Fibroblast Survival in 3D Bio-Printed Constructs - Kostenko, Anastassia; Swioklo, Stephen; Connon, Che J. (Frontiers in Mechanical Engineering, 2022)
The principle of three-dimensional (3D) bio-printing involves integration of biomaterials, live cells and controlled motor systems for creating complex biomimetic constructs. Bio-ink is one of the most important components in the process of 3D bio-printing and needs to be sufficiently viscous to be dispensed as a free-standing filament but be biocompatible to maintain cell viability and function. Alginate has been used widely for 3D bio-printing due to its biocompatibility, tunable properties, rapid gelation, low cost, and ability to be functionalized to direct cell behavior. By tuning the physiochemical parameters of alginate-based bio-inks, such as viscosity, improvements in print resolution, fidelity and growth characteristics of encapsulated cells can be achieved. This study aimed to improve the printability of low concentration alginate bio-inks by utilizing calcium sulphate (CaSO4) pre-crosslinking. A variety of alginates, differing in their viscosity, molecular weight and b-D-mannuronate and α-L-guluronate residues were investigated by wet spinning and bio-printing. Rheological and structural properties of pre-crosslinked alginates were characterized with the aim of mitigating the resolution problems associated with the use of low percentage alginate bio-inks, more favorable for maintaining cell viability. Pre-crosslinking produced a significant effect on viscosity of biomaterials improving their suitability for the bio-printing process and influencing the final resolution of the printed structure. Medium viscosity high b-D-mannuronate containing alginate (MVM) showed the highest degree of viscosity change compared to the control (p <0.0001; n=6), assessed by single value viscometry analysis and shear rheology, after pre-crosslinking and was subsequently used in experiments with cells. The survival of human corneal stromal fibroblasts (CSFs) was assessed using CellTiterGlo metabolic assay and confirmed with Calcein acetoxymethyl and Ethidium homodimer -1 live/dead staining in pre-crosslinked alginate fibers and bio-printed lattices. Encapsulation of CSFs in pre-crosslinked alginate-based bio-inks did not have a detrimental effect on CSF viability compared to the non-pre-crosslinked control over 7 days under standard cell culture conditions. Overall, printability of low percentage alginate bio-inks was improved by pre-crosslinking without affecting the biocompatibility of the bio-inks.